De Novo Designed Peptide and Protein Hairpins Self‐Assemble into Sheets and Nanoparticles. Issue 10 (15th February 2021) - Galloway, Johanna M.; Bray, Harriet E. V.; Shoemark, Deborah K.; Hodgson, Lorna R.; Coombs, Jennifer; Mantell, Judith M.; Rose, Ruth S.; Ross, James F.; Morris, Caroline; Harniman, Robert L.; Wood, Christopher W.; Arthur, Christopher; et al.
Abstract: The design and assembly of peptide‐based materials has advanced considerably, leading to a variety of fibrous, sheet, and nanoparticle structures. A remaining challenge is to account for and control different possible supramolecular outcomes accessible to the same or similar peptide building blocks. Here a de novo peptide system is presented that forms nanoparticles or sheets depending on the strategic placement of a "disulfide pin" between two elements of secondary structure that drive self‐assembly. Specifically, homodimerizing and homotrimerizing de novo coiled‐coil α‐helices are joined with a flexible linker to generate a series of linear peptides. The helices are pinned back‐to‐back, constraining them as hairpins by a disulfide bond placed either proximal or distal to the linker. Computational modeling indicates, and advanced microscopy shows, that the proximally pinned hairpins self‐assemble into nanoparticles, whereas the distally pinned constructs form sheets. These peptides can be made synthetically or recombinantly to allow both chemical modifications and the introduction of whole protein cargoes as required. Abstract : Homodimerizing and homotrimerizing α‐helical coiled‐coils are connected by a linker and joined back‐to‐back using a disulfide bond to make hairpin building blocks. Nanoparticles form when the pin is proximal to the loop, and flat sheets when pinned distal from the loop. These are made by peptide synthesis or with recombinant DNA, allowing decoration of assemblies with functional small molecules and proteins.